Populism and Political Parties in Asia: A Comparison of Aam Admi Party (AAP) in India and the Liberal Democratic Party (LDP) in Japan - Debasish Nandy; Md. Saifullah Akon (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2023)
Populism is one of the most popular techniques used by Asian political parties. Political parties use this tactic through socio-political movements not only for the larger good of society but also for their own narrow goals. This article investigates two separate political parties from India and Japan. Populist policies have both beneficial and harmful effects on politics. The given promises often failed to address the grievances of the voters. A significant civil society movement propelled the Aam Admi Party (AAP) to political status. It began as a non-political entity and evolved into a political one. Following the formation of AAP, the issue of civil society as a non-political entity arose. The AAP is a regional party that holds power in two Indian states, focusing its populist policies on local issues. As a national party, the Liberal Democratic Party of Japan (LDP) is comparatively old and addresses pertinent national issues, like national security. The quality of politics and socio-economic dynamics of the two countries are different. This paper argues that populism as a tool cannot always be beneficial for the political culture of a country. The wide gap between the promises and implementation often creates discontent among the voters. This paper will attempt the delineate the different scenarios of the populist policies of the AAP of India and the LDP of Japan using the content analysis method.